Engineered pine endophytic Bacillus toyonensis with nematocidal and colonization abilities for pine wilt disease control - Li, Dongzhen; Li, Yongxia; Wang, Xuan; Zhang, Wei; Wen, Xiaojian; Liu, Zhenkai; Feng, Yuqian; Zhang, Xingyao (Frontiers in Microbiology, 2023)
The pinewood nematode (PWN) is responsible for causing pine wilt disease (PWD), which has led to the significant decline of conifer species in Eurasian forests and has become a globally invasive quarantine pest. Manipulating plant-associated microbes to control nematodes is an important strategy for sustainable pest management. However, it has proven difficult to find pine-associated bacteria that possess both nematocidal activity and the ability to colonize pine tissues. This study isolated a Bacillus toyonensis strain Bxy19 from the healthy pine stem, which showed exceptional tolerance to turpentine and pine tissue extract in stress experiments. The strain was transformed into an engineered nematocidal strain, Bxy19P3C6, that expressed the Cry6Aa crystal protein. Additionally, a fluorescent strain Bxy19P3GFP was constructed to determine its dispersal ability in Pinus massoniana seedlings. The results showed that the fluorescent strain was observed to enter the needles of the seedlings through the stomata and colonize the vascular bundle after being sprayed on the seedlings. The strain was observed to colonize and spread in the tracheid after being injected into the stems. The strain could colonize the seedlings and persist for at least 50 days. Furthermore, the greenhouse experiments indicated that both spraying and injecting the engineered strains Bxy19P3C6 had considerable efficacy against nematode infection. The evidence of colonization ability and persistence of the strain in pine advances our understanding of the control and prediction of the colonization of exogenously delivered bacteria in pines. This study provides a promising approach for manipulating plant-associated bacteria and using Bt protein to control nematodes.